Incidence And Management of Complications Associated with Myocardial Infarction: Incidence and Management of Complications Associated With Myocardial Infarction - Ahsan Waqar, Muhammad; Riaz, Tehseen; Majeed , Imtiaz; Khurram, Mustafa; Waseem , Faiza; Mehboob, Tooba; Tabassam, Naila; Aslam, Rabia; Bashir, Irfan (Pakistan BioMedical Journal, 2022)
Coronary heart disease (CHD) is a major cause of morbidity and mortality all around the world. Incidence of the complications of myocardial infarction (MI) had decreased to less than 1% since invention of the percutaneous coronary intervention, although the mortality results from myocardial infarction had decreased in recent years, however the burden of this disease have not ceased. Modern treatment of MI is basically built on any of the clinical evidences that are based on many of the studies that have been studied from previous thirty years. Clinical practice’s evolution had significantly decreased morbidity or mortality linked by this disorder. Severe complications of the myocardial infarction include cardiogenic shock, inferior myocardial infarction, pericarditis and noteworthy right ventricular infarction. These complications are very rare; however, their reputation is neglected for the possible failure to manage early diagnosis and appropriate treatment. Inferior wall myocardial infarction accounts for 40- 50% of all the myocardial infarctions and are mostly seen as having a more promising diagnosis than the anterior wall infarctions. Pericarditis is the common disorder and a complication that arises after the myocardial infarction and has multiple causes. This is present in many secondary care and primary care settings. Frequently pericarditis has been often self-restricted, and the non-steroidal anti-inflammatory agents (NSAIDS) remains treatment of first line in the simple cases. Pharmacological management of complications includes beta blockers, Angiotensin Converting Enzyme Inhibitors, Antiplatelet Agents, and Non-Steroidal Anti-Inflammatory Drugs